A Weak Formulation for Solving the Elliptic Interface Problems with Imperfect Contact (Advances in Applied Mathematics and Mechanics, 2018)
We propose a non-traditional finite element method with non-body-fittinggrids to solve the matrix coefficient elliptic equations with imperfect contact in twodimensions, which has not been well-studied in the literature. Numerical experimentsdemonstrated the effectiveness of our method.